Islam, Modern Turkey, and a Javanese Intellectual: The Sutomo’s Visit to Turkey in 1937 - Machmudi, Yon; Supratman, Frial Ramadhan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
The early twentieth century served as a dynamic age for various modern movement intellectuals. The steamboat discovery enabled people to rush from one place to another, allowing a more active exchange of ideas and insights. Sutomo was a Javanese intellectual playing an essential role in Indonesia’s modern history. In 1936-1937 he travelled around the world and visited several countries, one of which was Turkey. This article discussed Sutomo’s views on modernization processes taking place in Turkey. This study employed a historical method by using articles from Soeara Oemoem’s newspaper from 1936-1937. That newspaper elaborately described Sutomo’s journey while he was in Turkey. In this article, we argued that social and economic situations influenced Sutomo’s views on Turkey’s modernization in the Dutch East Indies. His experiences abroad influenced his further involvement in the discourse of Indonesian secular and Islamic nationalism.